Cooperation, Collaboration, and Co-creation: A Review of Existing Literature and Applications - Nina Arina; Sonny Rustiadi (International Journal of Family Business Practices, 2018)
Innovation is a mechanism for entrepreneurs to create a product or service in accordance with company’s target market. While creating innovation, the company may not have some of the information or skills that are owned by the other parties or vice versa.As a solution, various approaches of cooperation, collaboration, or co-creation are chosen as the strategy to develop innovation. The purpose of this study is to examine the implementation of cooperation, collaboration, and co-creation as an entrepreneurial strategy. The method used is exploratory analysis by analysing the theory of Drucker (1993). The result of this research is a definitive differentiation of innovation for the four strategies. To conclude, the paper suggests the company to analyse their own ability and condition in order to create an innovation that will increase the productivity.